Computed tomography-guided percutaneous biopsy of pancreatic masses using pneumodissection - Tyng,Chiang Jeng (2013)
Objective To describe the technique of computed tomography-guided percutaneous biopsy of pancreatic tumors with pneumodissection. Materials and Methods In the period from June 2011 to May 2012, seven computed tomography-guided percutaneous biopsies of pancreatic tumors utilizing pneumodissection were performed in the authors' institution. All the procedures were performed with an automatic biopsy gun and coaxial system with Tru-core needles. The biopsy specimens were histologically assessed. Results In all the cases the pancreatic mass could not be directly approached by computed tomography without passing through major organs and structures. The injection of air allowed the displacement of adjacent structures and creation of a safe coaxial needle pathway toward the lesion. Biopsy was successfully performed in all the cases, yielding appropriate specimens for pathological analysis. Conclusion Pneumodissection is a safe, inexpensive and technically easy approach to perform percutaneous biopsy in selected cases where direct access to the pancreatic tumor is not feasible.